World geography affected by world upheavals - Tintero, Felipa L.; Manacsa, Felicitas R. (Quezon City, Philippines : Katha Publishing Co, Inc., 2002)
This book intends to provide an accurate picture of different peoples of the world and how environment affect their lives.
1. The Nature and content of geography -- 2. The Importance of maps -- 3. Map reading and map making -- 4. Land and water forms of the world -- 5. The American continent -- 6. Europe, the small continent with the greatest world impact -- 7. Africa : the emerging continent -- 8. Asia, the sleeping giant -- 9. Southwest Asia (The Middle East) : Hot spot of the world -- 10. The Philippines, meeting point of East and West.
Includes index.
Keywords: WORLD GEOGRAPHY